The Complexity and Diversity of Wicked Problems in School Contexts - Nguyen, Hong Thanh Thi (2018)
Hong, Nguyen T. T. 2018. The complexity and diversity of wicked problems in school contexts. Master’s Thesis in Education. University of Jyväskylä. Department of Education. Globalization is a hidden context for educational change, which results from the interplay among social, political, and economic matters. A lot of education reform and challenging problems in education was mentioned in twentieth century. However, little research on recent challenging problems has been done lately. That is the motivation for this study, which contributes to interpretation of most recent challenging problems, namely, wicked problems in education in twenty first century. Data for this research is taken from “Collaborative leadership processes in the changing education”’ (LED) project. First, the research on specific wicked problems in education are conducted in six educational organization. In addition, case study research is used to discuss the educational organizations’ contexts which relate to wicked problems. Then, the thematic inductive analysis is utilized to figure out the complexity and diversity of wicked problems in these organizations. Relating to complexity of wicked problems, results stated that wicked problems were not only harmful but also essential. In addition, wicked problems had either negative or positive impact to educational organization. Mentioning diversity of wicked problems, results showed that wicked problems were different if the variety existed in the schools while wicked problems were distinctively different if the difference involved competition among educational organizations. Teachers and students were main factors affected by wicked problems. However, schools did not have sufficient comprehension of their wicked problems. Therefore, helpful suggestions are presented in discussion part of this thesis in order to improve educational organizations’ situation. Keywords: globalization, challenging problems in education, wicked problems in school context, complexity of wicked problems, diversity of wicked problems